ESL students’ online and offline reading strategies: scrolling, clicking, flipping and reading / Izyani Mohamad Zaki, Fauziah Hassan and Abu Bakar Mohamed Razali - Mohamad Zaki, Izyani; Hassan, Fauziah; Mohamed Razali, Abu Bakar (ACRULeT, Faculty of Education & UiTM Press, 2008)
In this borderless world, computers and the Internet have become important tools of communication and learning and they have also become an important part of our lives. The opportunity to seek information through the computer has made reading an important language skill. Despite the importance of reading and technology, little research to date has been carried out to compare the reading strategies employed by readers when reading online compared to offline. Such studies are important because awareness of the similarities and differences on the strategies employed between these two modes of learning will enable teachers to help develop students’ reading ability. Hence, this study investigates if there is a difference between online and offline strategies used by second language readers. The participants in this study were ESL undergraduates at a university in Malaysia. The instrument employed was the Survey of Reading Strategies (SORS) (Sheorey and Mokhtari, 2001) and Online Survey of Register Strategies (OSORS) by Anderson (2003). These questionnaires tap three different types of information: global reading strategies, problem solving strategies, and support strategies. The results of the study are discussed in terms of their pedagogical implications in the L2 classroom.